Impacts of micro-emulsion system on polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) reduction from industrial boilers. (15th May 2016) - Pongpiachan, S.; Wiriwutikorn, T.; Rungruang, C.; Yodden, K.; Duangdee, N.; Sbrilli, A.; Gobbi, M.; Centeno, C.
Highlights: Reductions of PCDD/PCDF emissions from a boiler was observed. Micro-emulsion technology also reduces SO2 /CO and NOx /CO. This can be a promising technology for reducing dioxins. Abstract: Previous studies have raised public concerns regarding issues of adverse health impacts on human exposure to PCDDs/PCDFs. Industrial boilers have been criticized as one of the main contributors of PCDDs/PCDFs emissions. To minimize dioxin releases from unintentional production, a study on the best available techniques (BAT) and best environmental practices (BEP) was conducted using a micro-emulsion technology, which was developed for enhancing the combustion efficiency of industrial boilers. In this study, the performance of micro-emulsion technology on reducing PCDDs/PCDFs emissions from an industrial boiler using three types of fuels, 100% heavy fuel oil (100% HFO), 90% HFO coupled with 10% ethanol (90% HFO–10% ethanol), and 90% HFO coupled with 10% water (90% HFO–10% water), were carefully evaluated and statistically analyzed. The use of the ANOVA statistical method for the analysis of variance showed that there were no significant differences associated with the trace gaseous concentrations (e.g., CO, NOx, and SO2 ) among the three types of fuels. Furthermore, an industrial boiler using 90% HFO–10% ethanol tends to show the minimum PCDDs/PCDFs emissions in comparison with other two types of fuels. In addition, significant reductions of TCDDs, PeCDDs, HxCDDs, HpCDDs, TCDFs, PeCDFs, and total PCDDs were observed in an industrial boiler using the combination of HFO and ethanol. Overall, micro-emulsion can be considered a promising clean technology in term of PCDDs/PCDFs reduction.